Education Character in Learning Social Sciences in School Basic to The Independent Curriculum - Hasanah, Nurul; Salsabilla, Raisha (Journal of Elementary School Education, 2024)
This study aim Character education is part of shaping students' attitudes to become better. Social teachings are subjects that contain social life. The aim of this research is to analyze character formation in social studies learning in elementary schools with an independent program. This research method is a qualitative document study. The data collection techniques are literature reviews and internet research. Data was obtained from various articles reviewed by researchers. The result of this research is that learning social sciences in an independent program is combined with learning natural sciences which is now called IPAS. Character education in social studies and learning in independent learning programs can be done in a simple way, namely by making teachers good role models for students and implementing character values in educational projects created by teachers.